1985
DOI: 10.1007/bf00996201
|View full text |Cite
|
Sign up to set email alerts
|

Sound graphs: A numerical data analysis method for the blind

Abstract: A system for the creation of computer-generated sound patterns of two-dimensional line graphs is described. The objectives of the system are to provide the blind with a means of understanding line graphs in the holistic manner used by those with sight. A continuously varying pitch is used to represent motion in the x direction. To test the feasibility of using sound to represent graphs, a prototype system was developed and human factors experimenters were performed. Fourteen subjects were used to compare the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 8 publications
2
86
0
Order By: Relevance
“…This basic sonification technique has been successfully used to provide non-visual access to a variety of visual graph-based representations including line graphs (Mansur et al, 1985), seismograms (Hayward, 1992) and time series data (Flowers and Hauer, 1995). Mansur et al (1985) pioneered the technique when they developed sound graphs, which mapped data values on the y-axis of a line graph to continuous pitch and the x-axis to temporal presentation. They found that, after a small amount of training, users were able to identify key patterns in the underlying data such as linearity and symmetry on 79% to 95% of the trials.…”
Section: Auditory Graphsmentioning
confidence: 99%
“…This basic sonification technique has been successfully used to provide non-visual access to a variety of visual graph-based representations including line graphs (Mansur et al, 1985), seismograms (Hayward, 1992) and time series data (Flowers and Hauer, 1995). Mansur et al (1985) pioneered the technique when they developed sound graphs, which mapped data values on the y-axis of a line graph to continuous pitch and the x-axis to temporal presentation. They found that, after a small amount of training, users were able to identify key patterns in the underlying data such as linearity and symmetry on 79% to 95% of the trials.…”
Section: Auditory Graphsmentioning
confidence: 99%
“…For example, some attempts have been made to sonify numerical data for people with visual impairment; in some cases this is combined and/or compared with kinaesthetic methods used to represent the same data [8,9,10,11]. Perhaps one of the earliest studies was made by Mansur who used a sinusoidal wave, the frequency of which is used to sonify the ordinate value of a numerical function where the abscissa is mapped to time.…”
Section: Related Workmentioning
confidence: 99%
“…Perhaps one of the earliest studies was made by Mansur who used a sinusoidal wave, the frequency of which is used to sonify the ordinate value of a numerical function where the abscissa is mapped to time. Mansur discovered that mathematical concepts such as symmetry, monotonicity and the slopes of lines could be determined using sound after a relatively small amount of training [10]. Another related application domain involves the sonification of financial data [12,13,14].…”
Section: Related Workmentioning
confidence: 99%
“…the pitch of each piano note in the sequence) depends on the vertical relationship between O and S ( Figure 3, T is the FAS-TRACK transmitter). This is similar way to a standard Soundgraph [3,4] where the value on the y axis of the graph is mapped to pitch and the x axis to time. The follow-ing empirically derived equation gives the pitch of the streamed source (as a MIDI note number):…”
Section: Sound Mappingsmentioning
confidence: 99%
“…Being able to en-hance this existing material with dynamic feedback will improve its usefulness and usability. Our approach overlays the diagrams with non-speech audito information, based on the idea of Soundgraphs [3,4]. This is generic because we can overlay any existing diagrams with audio information.…”
Section: Introductionmentioning
confidence: 99%